The role of hospital environment and the hands of medical staff in the transmission of the Clostridioides (Clostridium) difficile infection - Monika Kabała; Małgorzata Aptekorz; Gajane Martirosian (Nofer Institute of Occupational Medicine, 2019)
This paper attempts to determine the role of the hospital environment in the spread of Clostridioides/Clostridium (C.) difficile infections based on a review of studies published in the medical literature and in the light of the authors' own experiences. Clostridioides/Clostridium difficile has recently attracted more and more attention, not only as an etiological factor of pseudomembranous intestinal inflammation and antibiotic associated diarrhea, but also as an etiologic factor of healthcare-associated infections (HAI) because of the possibility to survive in the hospital environment for a long time. This is caused by the production of spores, whose eradication options are limited. Clostridioides/Clostridium difficile spores are present not only on bedding of infected patients and their other belongings, but also on medical equipment and the hands of medical personnel, constituting a potential source of infection for other patients and some of the staff. The introduction of appropriate procedures for hand hygiene as well as for cleaning and disinfection of hospital surfaces makes it possible to reduce the number of spores and/or eradicate them. These procedures must be strictly followed to reduce the occurrence of spores in the hospital environment and to prevent further spread of C. difficile infections (CDI). Monitoring the presence of the C. difficile spores in a hospital environment using appropriate media (C diff Banana BrothTM) provides additional opportunities for culturing of C. difficile strains and determining ribotypes, especially hyperepidemic ones, which is extremely important from an epidemiological point of view. Med Pr. 2019;70(6):739-45